Nucleic Acid-Based Drug Delivery Strategies - Tan, Xuyu (J Control Release, 2020)
Nucleic acids have not been widely considered as an optimal material for drug delivery. Indeed, unmodified nucleic acids are enzymatically unstable, too hydrophilic for cell uptake and payload encapsulation, and may cause unintended biological responses such as immune system activation and prolongation of the blood coagulation pathway. Recently, however, three major areas of development surrounding nucleic acids have made it worthwhile to reconsider their role for drug delivery. These areas include DNA/RNA nanotechnology, multivalent nucleic acid nanostructures, and nucleic acid aptamers, which, respectively, provide the ability to engineer nanostructures with unparalleled levels of structural control, completely reverse certain biological properties of linear/cyclic nucleic acids, and enable antibody-level targeting using an all-nucleic acid construct. These advances, together with nucleic acids’ ability to respond to various stimuli (engineered or natural), have led to a rapidly increasing number of drug delivery systems with potential for spatiotemporally controlled drug release. In this review, we discuss recent progress in nucleic acid-based drug delivery strategies, their potential, unique use cases, and risks that must be overcome or avoided.